2015
DOI: 10.1016/j.msec.2015.05.071
|View full text |Cite
|
Sign up to set email alerts
|

Silver activation on thin films of Ag–ZrCN coatings for antimicrobial activity

Abstract: Nowadays, with the increase of elderly population and related health problems, knee and hip joint prosthesis are being widely used worldwide. However, failure of these invasive devices occurs in a high percentage thus demanding the revision of the chirurgical procedure. Within the reasons of failure, microbial infections, either hospital or subsequently-acquired, contribute in high number to the statistics. Staphylococcus epidermidis (S. epidermidis) has emerged as one of the major nosocomial pathogens associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 57 publications
3
42
0
Order By: Relevance
“…For example, Chu et al [48] observed that the antimicrobial performance of Ag-containing ZrTiAl and AlAgTi thin films is similar to that of a pure Ag coating. In several other studies Ag was incorporated as an element in thin films [49,50,51] to tune the antimicrobial performance, but the alteration of another parameter (roughness, size of crystal formation, etc.) makes it difficult to assess whether the killing effectiveness can be only attributed to compositional differences.…”
Section: Factors Responsible For Antimicrobial Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Chu et al [48] observed that the antimicrobial performance of Ag-containing ZrTiAl and AlAgTi thin films is similar to that of a pure Ag coating. In several other studies Ag was incorporated as an element in thin films [49,50,51] to tune the antimicrobial performance, but the alteration of another parameter (roughness, size of crystal formation, etc.) makes it difficult to assess whether the killing effectiveness can be only attributed to compositional differences.…”
Section: Factors Responsible For Antimicrobial Behaviourmentioning
confidence: 99%
“…In order to promote Ag ionisation, the oxidising compound sodium hypochlorite can be used in Ag-containing coatings. This process is called silver activation and has been successfully used to promote the antimicrobial effect of the coatings [49]. Another method for eliminating pathogens, photocatalysis disinfection using ultraviolet light, involves promoting the release of reactive oxygen species resulting from redox reactions at the surface of the TiO 2 films [59]; this also has self-cleaning properties [59,60,61].…”
Section: Factors Responsible For Antimicrobial Behaviourmentioning
confidence: 99%
“…Biomaterials used on hip arthroplasties were researched to identify their possible influence on biofilm formation prevention on hip prosthesis. The presence of factors that interfere on biofilm formation was evidenced: metal roughness, antibiotic coatings action, difference in biofilm adhesion on distinct biomaterials, ions action, different concentrations of titanium and silver, coating activity of HD-CLPE(VE) with PMPC and acylase activity in disrupting quorum-sensing signals (RAMAGE et al, 2003;PARVIZI et al, 2004;TOMÁŠ;NACHTNEBL;OTIEPKA, 2007;HENRIQUES et al, 2009;HOSMAN et al, 2009HOSMAN et al, , 2011NURYASTUTI et al, 2011;GÓMEZ-BARRENA et al, 2012;NEUT et al, 2012NEUT et al, , 2015LASS et al, 2014;FERRERI et al, 2015;KYOMOTO et al, 2015;GROVER et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies were performed to develop and evaluate new coatings with the ability to minimize microbial colonization (PARVIZI et al, 2004;HENRIQUES et al, 2009;LEWIS et al, 2010;NEUT et al, 2012NEUT et al, , 2015FERRERI et al, 2015;KYOMOTO et al, 2015;GROVER et al, 2016). Silver-zirconium carbonitride (Ag-ZrCN) thin films and cross-linked polyethylene combined with vitamin E-blended and a poly(2methacryloyloxyethyl phosphorylcholine) layer -(HD-CLPE(VE) with PMPC) coatings presented antimicrobial activity (FERRERI et al, 2015;KYOMOTO et al, 2015). Moreover, the biomaterial developed with an acylase-containing polyurethane coating disrupted quorum-sensing signals 1397 Hip prosthesis biomaterials… MARQUES, D. M. et al responsible by communication and progression of biofilm formation (GROVER et al, 2016).…”
Section: New Coatings With Antimicrobial Activitymentioning
confidence: 99%
“…Different materials have been used as coatings on implants in order to improve cell adhesion and to prevent their wear, such as: ultra-fine hydroxyapatite powders (Kaya, 2008), carbon nanotubes (Kaya, 2008), Ag-ZrCN films (Ferreri et al, 2015) and DLC films (Casiraghi et al, 2005). All these coatings have shown good results, however only the DLC thin film has been considered able to promote a reduction on metal friction at the same time that increases the wear resistance, the hardness, and the cell adhesion rate (Grill et al, 1988;Grill, 2003;Ianno et al, 1995;Jelinek et al, 2016;Khatir et al, 2015;Marciano et al, 2009).…”
Section: Introductionmentioning
confidence: 99%